Gold-catalyzed naphthalene functionalization - Pérez, Pedro J.; Díaz-Requejo, M. Mar; Rivilla, Iván (Beilstein Journal of Organic Chemistry, 2011)
The complexes IPrMCl (IPr = 1,3-bis(diisopropylphenyl)imidazol-2-ylidene, M = Cu, 1a; M = Au, 1b), in the presence of one equiv of NaBAr'4 (Ar' = 3,5-bis(trifluoromethyl)phenyl), catalyze the transfer of carbene groups: C(R)CO2Et (R = H, Me) from N2C(R)CO2Et to afford products that depend on the nature of the metal center. The copper-based catalyst yields exclusively a cycloheptatriene derivative from the Buchner reaction, whereas the gold analog affords a mixture of products derived either from the formal insertion of the carbene unit into the aromatic C–H bond or from its addition to a double bond. In addition, no byproducts derived from carbene coupling were observed.
Keywords: carbene insertion; copper catalysts; diazoacetates; gold catalysts; naphthalene functionalization; selective insertion